2005
DOI: 10.1161/01.str.0000179044.37760.9d
|View full text |Cite
|
Sign up to set email alerts
|

Role of Adenosine and Nitric Oxide on the Mechanisms of Action of Dipyridamole

Abstract: Background and Purpose-The combination of dipyridamole and aspirin has been shown to be more effective than aspirin alone in the secondary prevention of stroke. Dipyridamole may act by inhibiting adenosine uptake, thus potentiating its actions. Dipyridamole also inhibits cGMP-specific phosphodiesterases (PDE) and, through this mechanism, could potentiate cGMP-mediated actions of nitric oxide. Methods-To define the mechanism of action of dipyridamole, we studied the local vascular effects of adenosine, acetylch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
8

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 44 publications
1
28
0
8
Order By: Relevance
“…We and others have shown previously that dipyridamole very effectively inhibits the uptake of adenosine into red cells in whole blood 11,25,26 and thereby leaves the adenosine available to interact with platelets. 27,28 Once again, very similar results were obtained irrespective of the type of P2Y 12 antagonist used.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…We and others have shown previously that dipyridamole very effectively inhibits the uptake of adenosine into red cells in whole blood 11,25,26 and thereby leaves the adenosine available to interact with platelets. 27,28 Once again, very similar results were obtained irrespective of the type of P2Y 12 antagonist used.…”
Section: Discussionsupporting
confidence: 64%
“…We have already discussed the ability of dipyridamole to inhibit adenosine uptake into red cells, but in addition to its inhibitory effects on adenosine uptake, dipyridamole is also an inhibitor of cAMP phosphodiesterase. 27,28 cAMP phosphodiesterase inhibitors inhibit platelet function by preventing the breakdown of cAMP, thus helping to maintain elevated intracellular levels of the nucleotide. Thus, in the presence of adenosine, this additional property could bring about even further inhibition of platelet aggregation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, DP has been shown to potentiate NO/cGMP vasodilatory and platelet antiaggregatory effects, 40 enhance ischemia-induced angiogenesis, 41 increase myocardial perfusion in heart failure and stable coronary artery disease, 21,42 and ameliorate the severity of ischemic strokes via NO-and adenosine-mediated effects. 43 …”
Section: Potentiation Of No-mediated Pathwaysmentioning
confidence: 99%
“…In the present study, we further demonstrated that, in the presence of adenosine, an ATP-induced [Ca 2+ ]i response was observed in arteriole smooth muscle cells -although this reaction was partially inhibited. Because adenosine A1 receptors mediate the inhibition of L-type Ca 2+ channels (Di Perri et al, 1989;Rocher et al, 1999), the effects of dipyridamole on resistance vessels may be partly explained by the potentiation of adenosine mechanisms rather than the potentiation of NO or other cGMP-mediated actions (Gamboa et al, 2005).…”
Section: Response Of Smooth Muscle Cells In Testicular Arterioles Witmentioning
confidence: 99%